2021
DOI: 10.1136/bmjgh-2021-006809
|View full text |Cite
|
Sign up to set email alerts
|

Regional and socioeconomic disparities in cardiovascular disease in Canada during 2005–2016: evidence from repeated nationwide cross-sectional surveys

Abstract: IntroductionThe objective of this study is to examine the temporal trends and patterns of regional and socioeconomic disparities in cardiovascular disease (CVD) in Canada during 2005–2016.MethodsA total of 670 000 adults aged ≥20 years who participated in the Canadian Community Health Surveys between 2005 and 2016 were enrolled for this study. CVD referred to heart disease and stroke in this study. Equivalised household income was used as a proxy of socioeconomic status. Absolute and relative socioeconomic ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Such initiatives can empower individuals to adopt healthier lifestyles, cultivate cardiovascular wellness and mitigate the risk factors associated with CVD and its comorbidities 38 39. Different from other countries such as Canada, our study reveals a notable gender difference in CVD prevalence, with a higher incidence observed among women than men among individuals aged ≥60 years 10. This difference highlights the significance of considering unique population characteristics and healthcare contexts in CVD research.…”
Section: Discussionmentioning
confidence: 65%
“…Such initiatives can empower individuals to adopt healthier lifestyles, cultivate cardiovascular wellness and mitigate the risk factors associated with CVD and its comorbidities 38 39. Different from other countries such as Canada, our study reveals a notable gender difference in CVD prevalence, with a higher incidence observed among women than men among individuals aged ≥60 years 10. This difference highlights the significance of considering unique population characteristics and healthcare contexts in CVD research.…”
Section: Discussionmentioning
confidence: 65%
“…By contrast, physical activity was similar across the regions and not a contributor to the high risk of stroke in South Eastern USA ( 14 ). In Canada, isolated hot spot exists in rural Canada rather than stroke belt phenomenon ( 9 ). A consistent theme is the association of stroke among regions with lower socioeconomic group even though the distribution of socioeconomic groups has remained stable ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, isolated hot spot exists in rural Canada rather than stroke belt phenomenon ( 9 ). A consistent theme is the association of stroke among regions with lower socioeconomic group even though the distribution of socioeconomic groups has remained stable ( 9 ). In Denmark, stroke and heart disease rates are higher on the Eastern part of Zealand than Eastern part of Jutland ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Running regularly is associated with reduced risk of cardiovascular disease, type 2 diabetes, and obesity [ 10 , 11 , 12 , 13 ]. At the same time that recreational running is increasing [ 6 , 14 ], so is sedentary behavior [ 15 , 16 , 17 , 18 ], which has the potential to undo benefits from running. Therefore, health initiatives have identified recreational running as an effective means to promote active populations and lower risks associated with physical inactivity [ 14 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%